Developing a new host-vector system for Deinococcus grandis - Sakai, Miyabi; Shimosaka, Taichi; Katsumata, Kosuke; Yohda, Masafumi; Narumi, Issay (Frontiers in Microbiology, 2024)
Deinococcus spp. are known for their radiation resistance, toxic compound removal, and production of valuable substances. Therefore, developing gene expression systems for Deinococcus spp. is crucial in advancing genetic engineering applications. To date, plasmid vectors that express foreign genes in D. radiodurans and D. geothermalis have been limited to plasmid pI3 and its derivatives. In contrast, plasmid vectors that express foreign genes in D. grandis include plasmid pZT23 and its derivatives. In this study, we developed a new system for the stable introduction and retention of expression plasmids for D. grandis. Two cryptic plasmids were removed from the wild-type strain to generate the TY3 strain. We then constructed a shuttle vector plasmid, pGRC5, containing the replication initiation region of the smallest cryptic plasmid, pDEGR-3, replication initiation region of the E. coli vector, pACYC184, and an antibiotic resistance gene. We introduced pGRC5, pZT23derived plasmid pZT29H, and pI3-derived plasmid pRADN8 into strain TY3, and found their coexistence in D. grandis cells. The quantitative PCR assay results found that pGRC5, pZT29H, and pRADN8 had relative copy numbers of 11, 26, and 5 per genome, respectively. Furthermore, we developed a new plasmid in which the luciferase gene was controlled by the promoter region, which contained radiation-desiccation response operator sequences for D. grandis DdrO, a stress response regulon repressor in D. grandis, hence inducing gene expression via ultraviolet-C light irradiation. These plasmids are expected to facilitate the removal and production of toxic and valuable substances, in D. grandis, respectively, particularly of those involving multiple genes.